2013
DOI: 10.1210/me.2012-1256
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Leydig and Sertoli Cells to Testosterone Production in Mouse Fetal Testes

Abstract: Testosterone is a final product of androgenic hormone biosynthesis, and Leydig cells are known to be the primary source of androgens. In the mammalian testis, two distinct populations of Leydig cells, the fetal and the adult Leydig cells, develop sequentially, and these two cell types differ both morphologically and functionally. It is well known that the adult Leydig cells maintain male reproductive function by producing testosterone. However, it has been controversial whether fetal Leydig cells can produce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(186 citation statements)
references
References 44 publications
12
166
0
Order By: Relevance
“…in testosterone production prior to puberty (O'Shaughnessy et al, 2000;Shima et al, 2013). We conclude that, following initial specification, the FLC population is retained and apparently functions relatively normally, independent of SC, GC and PTMC input in fetal and neonatal life.…”
Section: Flcs Function Independently In the Neonatal Testismentioning
confidence: 75%
“…in testosterone production prior to puberty (O'Shaughnessy et al, 2000;Shima et al, 2013). We conclude that, following initial specification, the FLC population is retained and apparently functions relatively normally, independent of SC, GC and PTMC input in fetal and neonatal life.…”
Section: Flcs Function Independently In the Neonatal Testismentioning
confidence: 75%
“…First, MAMLD1 deficiency may compromise fetal Leydig cell function around the critical period for sex development, leading to 46,XY DSD with hypospadias because of reduced but not abolished T production, as has been proposed previously [1]. In this regard, recent mouse studies have indicated that prenatal T biosynthesis requires both fetal Leydig cells that produce ∆4-androstenedione and Sertoli cells that express Hsd17b3 for the conversion of ∆4-androstenedione into T [20], although such Sertoli cell-specific HSD17B3 expression has not been demonstrated in human fetuses. Thus, in contrast to Mamld1 knockout mice [8], if Sertoli cell function is also compromised in affected patients, this would also contribute to defective T production during fetal life of affected patients.…”
Section: Case Reportsmentioning
confidence: 92%
“…Adult Leydig cells maintain androgen production throughout adulthood, functionally replacing fetal Leydig cells (Griswold and Behringer, 2009;Habert et al, 2001). Despite their similar functions in producing androgens, fetal and adult Leydig cells exhibit many differences in their transcriptomes (Dong et al, 2007;Shima et al, 2013), morphology (Haider, 2004) and regulation (Agelopoulou et al, 1984;Aubert et al, 1985;Baker and O'Shaughnessy, 2001;Dong et al, 2007;El-Gehani et al, 1998;Gangnerau and Picon, 1987;Ma et al, 2004;Majdic et al, 1998;O'Shaughnessy et al, 1998;Patsavoudi et al, 1985;Zhang et al, 2001). These differences between fetal and adult Leydig cells led to the hypothesis that the two Leydig cell populations are in fact distinct cell lineages arising from separate origins (Baker et al, 1999;Haider, 2004;Kerr and Knell, 1988;Lording and De Kretser, 1972;O'Shaughnessy et al, 2003;O'Shaughnessy and Fowler, 2011;Roosen-Runge and Anderson, 1959;Shima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their similar functions in producing androgens, fetal and adult Leydig cells exhibit many differences in their transcriptomes (Dong et al, 2007;Shima et al, 2013), morphology (Haider, 2004) and regulation (Agelopoulou et al, 1984;Aubert et al, 1985;Baker and O'Shaughnessy, 2001;Dong et al, 2007;El-Gehani et al, 1998;Gangnerau and Picon, 1987;Ma et al, 2004;Majdic et al, 1998;O'Shaughnessy et al, 1998;Patsavoudi et al, 1985;Zhang et al, 2001). These differences between fetal and adult Leydig cells led to the hypothesis that the two Leydig cell populations are in fact distinct cell lineages arising from separate origins (Baker et al, 1999;Haider, 2004;Kerr and Knell, 1988;Lording and De Kretser, 1972;O'Shaughnessy et al, 2003;O'Shaughnessy and Fowler, 2011;Roosen-Runge and Anderson, 1959;Shima et al, 2013). In fact, multiple origins of fetal Leydig cells have been suggested, including Sf1 + nonsteroidogenic interstitial cells originating from the gonadal primordium (Barsoum et al, 2013;Barsoum and Yao, 2010), mesonephros (Merchant-Larios and Moreno-Mendoza, 1998;Val et al, 2006), neural crest (Mayerhofer et al, 1996), coelomic epithelium (Karl and Capel, 1998), and cells residing in the border between gonad and mesonephros (DeFalco et al, 2011).…”
Section: Introductionmentioning
confidence: 99%